SAUR proteins and PP2C.D phosphatases regulate H+-ATPases and K+ channels to control stomatal movements. Issue 1 (19th November 2020) - Wong, Jeh Haur; Klejchová, Martina; Snipes, Stephen A; Nagpal, Punita; Bak, Gwangbae; Wang, Bryan; Dunlap, Sonja; Park, Mee Yeon; Kunkel, Emma N; Trinidad, Brendan; Reed, Jason W; Blatt, Michael R; et al.
Abstract: Activation of plasma membrane (PM) H + -ATPase activity is crucial in guard cells to promote light-stimulated stomatal opening, and in growing organs to promote cell expansion. In growing organs, SMALL AUXIN UP RNA (SAUR) proteins inhibit the PP2C.D2, PP2C.D5, and PP2C.D6 (PP2C.D2/5/6) phosphatases, thereby preventing dephosphorylation of the penultimate phosphothreonine of PM H + -ATPases and trapping them in the activated state to promote cell expansion. To elucidate whether SAUR–PP2C.D regulatory modules also affect reversible cell expansion, we examined stomatal apertures and conductances of Arabidopsis thaliana plants with altered SAUR or PP2C.D activity. Here, we report that the pp2c.d2/5/6 triple knockout mutant plants and plant lines overexpressing SAUR fusion proteins exhibit enhanced stomatal apertures and conductances. Reciprocally, saur56 saur60 double mutants, lacking two SAUR genes normally expressed in guard cells, displayed reduced apertures and conductances, as did plants overexpressing PP2C.D5 . Although altered PM H + -ATPase activity contributes to these stomatal phenotypes, voltage clamp analysis showed significant changes also in K + channel gating in lines with altered SAUR and PP2C.D function. Together, our findings demonstrate that SAUR and PP2C.D proteins act antagonistically to facilitate stomatal movements through a concerted targeting of both ATP-dependent H + pumping and channel-mediated K + transport. Abstract : SMALL AUXIN UP RNA (SAUR) proteins and PP2C.D phosphatases antagonistically regulate stomatal aperture in Arabidopsis by modulating the activities of plasma membrane H + -ATPases and K + channels.